The Method of Imaginative Suggestion Assisted by the Short Film “Bapak” in Teaching Short Story Writing - Rukaya; Emah Khuzaemah; Rianto (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This study aims to determine the effectiveness of the Imagination Suggestion method assisted by the short film media